Hak-Hak Tersangka dalam Proses Penyidikan: Studi Kasus di Polda Sulawesi Selatan - Susi Aryani Manangin; Abd. Rasjak (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
This study aims to analyze the position of the suspect forgery of documentary instruments of evidence of land rights in the investigation process at the Directorate of the General Criminal Investigation of South Sulawesi Regional Police. This research combines normative juridical and empirical research methods. The primary data were collected using direct interviews, while the secondary data was collected using literature study techniques. The data obtained in this research were then analyzed qualitatively to describe problems and answer study purposes. The results show that the suspect forgery of documentary instruments of evidence of land rights still gets human rights protection in the investigation process. Investigators still prioritize humanitarian action by upholding the dignity of the suspects. The rights fulfilled by the Directorate of the General Criminal Investigation, South Sulawesi Regional Police, against suspects at each stage of an investigation include: the right to be examined promptly; self-defense; freely provide information; obtain an interpreter; obtain assistance from lawyers or legal advisers; and maintain physical and psychological health. Therefore, it is recommended that all Police investigators continue to implement investigative procedures for all criminal cases while upholding the dignity of suspects as legal subjects. On the other hand, a suspect must be cooperative and use the right to freely provide information to prove their innocence in the investigation process. In this case, the Directorate of the General Criminal Investigation of South Sulawesi Regional Police has applied the accusatory principle to realize a balanced investigation as regulated in Law No. 8 of 1981.